Pool oscillations and cast variations - penetration control for orbital tig welding of austenitic stainless steel tubing. - Woodward, Neil J. (Cranfield University, 1997)
Pool oscillations in tungsten inert gas welding pools have been used in a closed- loop control system for orbital welding of ultra high purity tubing, determining a target level of penetration by altering the welding current in real-time. The technique is ideally suited to this application since it is does not contravene the cleanliness requirements for the inner bore and can be implemented outside the small orbital heads that are commonly used. The results presented in this thesis show how clear pool oscillation signals in extremely small molten pools can be monitored by optimising the welding conditions and signal processing of the arc voltage signal. As an indicator of the likely variation in cast behaviour present particularly in austenitic stainless steels, a 'time-to-penetrate' characterisation was made of the materials, using the time of the transition from the Mode 1 to the Mode 3 oscillation behaviour as the measured variable. By applying the test across a range of welding currents, significant insight was obtained into the cast and associated penetration behaviour. Late transitions indicated casts that exhibited significantly different responses to the more usually applied welding procedures, especially at the lower levels of welding current (highlighting their potentially more problematic penetration behaviour). It was shown that the established theoretical models were difficult to apply with certainty to moving weld pools, and consequently a fuzzy logic model was used in the control strategy. The closed-loop system comprised a user-interface PC, a control rack and commercial welding power source - control signals were applied every 2 to 3 Hz. Mode 3 pool oscillations were found to offer a more than satisfactory sensitivity to the inner bead width created for the various casts of 1.65 mm wall thickness materials studied.